Evaluasi Pengelolaan Arsip Dinamis Bagian Tata Usaha Kantor Suku Dinas Lingkungan Hidup Kota Administrasi Jakarta Pusat - Amanda Rezki Ananda; Sri Kartikowati; Rizki Firdausi Rachmadania (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2026)
Archive management plays a crucial role in supporting orderly administration and smooth office operations. However, various obstacles remain in its implementation that impact the effectiveness of archive management. This study aims to evaluate archive management in the Administration Section of the Central Jakarta City Environmental Sub-Department Office, encompassing the implementation of management, the obstacles encountered, and recommendations for improvement. This study employed a qualitative method with a descriptive approach to describe the actual conditions of archive management in the field. Data were obtained through observation, interviews, and documentation as primary data, supported by relevant secondary data. The results indicate that archive management has been implemented through the stages of creation, use, maintenance, and reduction of archives. The creation and use stages have been carried out according to administrative procedures, but at the maintenance stage, there are still limitations in facilities, such as the lack of temperature and humidity control in the archive room. In addition, archive reduction has not been carried out optimally, resulting in an accumulation of archives. The main obstacles faced include limited human resources with competency in the field of archives and limited facilities and infrastructure. The implications of this study indicate the need to improve storage facilities and human resource competencies to achieve more effective and efficient archive management..